Teaching evidence-based decision-making. - Sevdalis, N; McCulloch, P (2006)
Evidence-based decision-making is important in surgery, but the nature of the work makes it difficult. Teaching it requires an interactive approach with a clinical team willing to consider it seriously,and to derive practical solutions. Decision-making and its influences must be understood, so that surgeons have a realistic idea of the role of evidence. Cognitive factors are particularly important.Strategies developed in the context of this knowledge are more likely to be adopted and used. Experts must be involved in searching for evidence and members of the management team in the learning process, the former to provide expertise on searching,the latter to ensure that the reasons for proposed changes are understood and treated sympathetically by those with financial control.